Show that $$\int_0^{\frac\pi2} \ln^3(\sin(x)) \, dx = -\frac\pi2 \ln^3(2) - \frac{\pi^3}8 \ln(2) - \frac{3\pi}4 \zeta(3)$$

I have seen a method for this elsewhere, but I would specifically like to reproduce this result in the same way I've computed the similar integrals of $\ln(\cos(x))\ln(\sin(x))$ and $\ln^2(\sin(x))$, as shown here and here - which involves a "complicated series", as Jack puts it.

In particular, I want to use the Fourier series

$$f(x) = \ln(\sin(x)) = -\ln(2) - \sum_{k=1}^\infty \frac{\cos(2kx)}k$$

Expanding the integrand yields

$$\begin{align*} -f(x)^3 &= \ln^3(2) + 3 \ln^2(2) \sum_{a=1}^\infty \frac{\cos(2ax)}a \\ &\quad + 3\ln(2) \left(\sum_{a=1}^\infty \frac{\cos^2(2ax)}{a^2} + 2 \sum_{a\neq b} \frac{\cos(2ax) \cos(2bx)}{ab}\right) \\ & \quad + \left(\sum_{a=1}^\infty \frac{\cos^3(2ax)}{a^3} + 3 \sum_{a\neq b} \frac{\cos^2(2ax) \cos(2bx)}{a^2b} + 6 \sum_{a\neq b\neq c} \frac{\cos(2ax) \cos(2bx) \cos(2cx)}{abc}\right) \end{align*}$$

In the integral, the series with $\cos(2ax)$ vanishes; by orthogonality, $\cos(2ax)\cos(2bx)$ vanishes; in combination of both of these facts, $\cos^2(2ax)\cos(2bx)$ and $\cos^3(2ax)$ also vanish. So the integral reduces to

$$\int_0^{\frac\pi2} f(x)^3 \, dx = -\frac\pi2 \ln^3(2) - \frac{\pi^3}8 \ln(2) - 6 \sum_{a\neq b\neq c} \frac1{abc} \int_0^{\frac\pi2} \cos(2ax) \cos(2bx) \cos(2cx) \, dx$$

In the remaining integral, I'm fairly sure that most of the terms integrate to $0$ using the orthogonality argument, except in the case of $a+b=c$,

$$\int_0^{\frac\pi2} \cos(2ax) \cos(2bx) \cos(2(a+b)x) \, dx \\ = \int_0^{\frac\pi2} \frac{\cos(2(a-b)x)\cos(2(a+b)x) + \cos^2(2(a+b)x)}2 \, dx = \frac\pi8$$

ETA: If there are no other triples, then I should end up with

$$-6 \sum_{a\neq b\neq c} \frac1{abc} \int_0^{\frac\pi2} \cos(2ax) \cos(2bx) \cos(2cx) \, dx = -\frac{3\pi}4 \sum_{a+b=c} \frac1{abc} = -\frac{3\pi}4 \zeta(3) \\ \implies \sum_{a\neq b} \frac1{ab(a+b)} = \zeta(3)$$


$$\begin{align*} \sum_{a\neq b} \frac1{ab(a+b)} &= \sum_{(a,b)\in\Bbb N^2} \frac1{ab(a+b)} - \frac12 \sum_{a=1}^\infty \frac1{a^3} \\[1ex] &= 2 \sum_{a<b} \frac1{ab(a+b)} - \frac12 \zeta(3) \\[2ex] \sum_{a<b} \frac1{ab(a+b)} &= \sum_{b=2}^\infty \frac1{b(b+1)} + \sum_{b=3}^\infty \frac1{2b(b+2)} + \sum_{b=4}^\infty \frac1{3b(b+3)} + \cdots \\[1ex] &= \sum_{b=2}^\infty \left(\frac1b - \frac1{b+1}\right) + \frac14 \sum_{b=3}^\infty \left(\frac1b - \frac1{b+2}\right) + \frac19 \sum_{b=4}^\infty \left(\frac1b - \frac1{b+3}\right) + \cdots \\[1ex] &= (H_2 - H_1) + \frac{H_4 - H_2}4 + \frac{H_6 - H_3}9 + \cdots \\[1ex] &= \sum_{n=1}^\infty \frac{H_{2n} - H_n}{n^2} \\[1ex] &= \sum_{n=1}^\infty \frac{H_{2n}}{n^2} - 2\zeta(3) \end{align*}$$

where the last equality is due to (31), and it remains to show

$$\sum_{n=1}^\infty \frac{H_{2n}}{n^2} = \frac{11}4 \zeta(3)$$

Rewriting the sum as follows leads me to think there may be a hidden Cauchy product, but I have not been able to find a decomposition.

$$H_{2n}-H_n = \sum_{k=1}^{2n} \frac1k - \sum_{k=1}^n \frac1k = \sum_{k=n+1}^{2n} \frac1k = \sum_{k=1}^n \frac1{n+k} \\ \implies\sum_{n=1}^\infty \frac{H_{2n}-H_n}{n^2} = \sum_{n=1}^\infty \sum_{m=1}^n \frac1{n^2(n+m)}$$

  • $\begingroup$ The notation is ambiguous: $\ln(\ln(\ln(\sin(x))))$ or $\ln(\sin(x))\cdot\ln(\sin(x))\cdot\ln(\sin(x))$ ? $\endgroup$
    – mr_e_man
    Jul 14, 2022 at 19:59
  • 4
    $\begingroup$ Most commonly, it means $(\ln(\sin(x))^3$, same as how $\sin^3(x)$ typically means $(\sin(x))^3$. $\endgroup$ Jul 14, 2022 at 20:02
  • $\begingroup$ I think there is a typo in your first line: the second term should be $-\frac{\pi^3}{8}\ln(2)$ $\endgroup$
    – MathFail
    Jul 14, 2022 at 21:32

3 Answers 3


Use a general method in this post:

$$ \begin{align} &\int_0^{\pi/2}\log^a(\sin(x))\log^b(\cos(x))\,\mathrm{d}x\\[3pt] =&\int_0^1\frac{\log^a(x)\log^b\left(\sqrt{1-x^2}\right)}{\sqrt{1-x^2}}\,\mathrm{d}x\tag{6a}\\[3pt] =&\frac1{2^{a+b+1}}\int_0^1\frac{\log^a(x)\log^b(1-x)}{\sqrt{x(1-x)}}\,\mathrm{d}x\tag{6b}\\ =&\frac{\partial_1^a\partial_2^b\mathrm{B}\!\left(\frac12,\frac12\right)}{2^{a+b+1}}\tag{6c} \end{align} $$


$$ \begin{align} \partial_x\mathrm{B}\!\left(x+\tfrac12,y+\tfrac12\right) &=A_{1,0}(x,y)\,\mathrm{B}\!\left(x+\tfrac12,y+\tfrac12\right)\tag{4a}\\[9pt] \partial_y\mathrm{B}\!\left(x+\tfrac12,y+\tfrac12\right) &=A_{0,1}(x,y)\mathrm{B}\!\left(x+\tfrac12,y+\tfrac12\right)\tag{4b}\\[9pt] \partial_xA_{n,m}(x,y) &=A_{n+1,m}(x,y)\tag{4c}\\[9pt] \partial_yA_{n,m}(x,y) &=A_{n,m+1}(x,y)\tag{4d} \end{align} $$


$$ \begin{align} \mathrm{B}\!\left(\tfrac12,\tfrac12\right) &=\pi\tag{5a}\\[9pt] A_{1,0}(0,0)&=A_{0,1}(0,0) =-2\log(2)\tag{5b}\\[6pt] A_{n,0}(0,0)&=A_{0,n}(0,0) =\frac{(n-1)!}{(-1)^{n-1}}\left(2-2^n\right)\zeta(n)&\text{for }n\ge2\tag{5c}\\ A_{n,m}(0,0) &=\frac{(m+n-1)!}{(-1)^{m+n-1}}\zeta(m+n)&\text{for }m,n\ge1\tag{5d} \end{align} $$

For simple, we use abbreviated notations, use $\mathrm{B}$ for $\mathrm{B}\!\left(\frac12,\frac12\right)$, and use $A_{n,m}$ for $A_{n,m}(0,0)$.


$$\begin{align} \int_0^{\frac{\pi}{2}} \ln^3(\sin(x)) dx &=\frac{1}{2^{3+1}}\cdot\partial_1^3 \mathrm{B}\\ &=\frac{1}{16}\cdot\partial_1^2 (A_{1,0}\mathrm{B})\\ &=\frac{1}{16}\cdot\partial_1 (A_{2,0}\mathrm{B}+A_{1,0}A_{1,0}\mathrm{B})\\ &=\frac{1}{16}\cdot\partial_1 (A_{2,0}\mathrm{B}+A^2_{1,0}\mathrm{B})\\ &=\frac{1}{16}\cdot(A_{3,0}\mathrm{B}+A_{2,0}A_{1,0}\mathrm{B}+2A_{1,0}A_{2,0}\mathrm{B}+A^2_{1,0}A_{1,0}\mathrm{B})\\ &=\frac{1}{16}\cdot(A_{3,0}+3A_{1,0}A_{2,0}+A^3_{1,0})\mathrm{B} \end{align}$$

Plug in values: $$\mathrm{B}=\mathrm{B}\!\left(\frac12,\frac12\right)=\pi,~~A_{1,0}=-2\ln(2),~~A_{2,0}=2\zeta(2)=\frac{\pi^2}{3},~~A_{3,0}=-12\zeta(3)$$

$$\begin{align} \int_0^{\frac{\pi}{2}} \ln^3(\sin(x)) dx&=\frac{\pi}{16}(-12\zeta(3)-2\pi^2\ln(2)-8\ln^3(2))\\ \int_0^{\frac{\pi}{2}} \ln^3(\sin(x)) dx&=-\frac{3\pi}{4}\zeta(3)-\frac{\pi^3}{8}\ln(2)-\frac{\pi}{2}\ln^3(2) \end{align}$$


$$\sum_{n=1}^\infty (-1)^{n+1}\frac{H_n^2-H_n^{(2)}}{n+1}\cos(2(n+1)x)\\ =\Re\sum_{n=1}^\infty \frac{H_n^2-H_n^{(2)}}{n+1}(-e^{2ix})^{n+1}$$

$$=\Re\left\{-\frac13 \ln^3(1+e^{2ix})\right\}$$

$$=x^2\ln(2\cos x)-\frac13\ln^3(2\cos x)\tag{*}$$

where we used the generating function

$$\sum_{n=1}^\infty \frac{H_n^2-H_n^{(2)}}{n+1}x^{n+1}=-\frac13\ln^3(1-x)$$

which follows from integrating

$$\sum_{n=1}^\infty (H_n^2-H_n^{(2)})x^{n}=\frac{\ln^2(1-x)}{1-x}.$$

Integrate both sides of $(*)$ from $x=0\to \pi/2$, $$\int_0^{\pi/2}\left[x^2\ln(2\cos x)-\frac13\ln^3(2\cos x)\right]dx$$

$$=\sum_{n=1}^\infty (-1)^{n+1}\frac{H_n^2-H_n^{(2)}}{n+1}\int_0^{\pi/2}\cos(2(n+1)x)dx$$

$$=\sum_{n=1}^\infty (-1)^{n+1}\frac{H_n^2-H_n^{(2)}}{n+1}\left(-\frac{\sin(n\pi)}{2(n+1)}\right)=0$$

so $$\int_0^{\pi/2}\ln^3(2\cos x)dx=3\int_0^{\pi/2}x^2\ln(2\cos x)dx=-\frac34\pi\zeta(3).$$

Note that $\int_0^{\pi/2}\ln^3(2\sin x)dx=\int_0^{\pi/2}\ln^3(2\cos x)dx.$


Some of the last several steps I took in the OP are unnecessary. The last obstacle is the sum

$$\sum_{(a,b)\in\Bbb N^2} \frac1{ab(a+b)} = \sum_{a=1}^\infty \sum_{b=1}^\infty \frac1{ab(a+b)} = \Gamma(3)\zeta(3) = 2\zeta(3)$$


$$f(x) = \sum_{a=1}^\infty \sum_{b=1}^\infty \frac{x^{a+b}}{ab(a+b)}$$

Then for $|x|<1$,

$$\begin{align*} f'(x) &= \sum_{a=1}^\infty \sum_{b=1}^\infty \frac{x^{a+b-1}}{ab} \\[1ex] x f'(x) &= \sum_{a=1}^\infty \sum_{b=1}^\infty \frac{x^{a+b}}{ab} \\[1ex] &= \sum_{a=1}^\infty \left(\frac{x^a}a \sum_{b=1}^\infty \frac{x^b}b\right) \\[1ex] &= \ln^2(1-x) \\[2ex] f'(x) &= \frac{\ln^2(1-x)}x \\[2ex] f(x) &= \int_0^x \frac{\ln^2(1-y)}y \, dy \end{align*}$$

and the result follows. (Incidentally, this is a proof I had come across on this site several months ago but am unable to track it down.)


You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .